The Authority Analysis of Non-Legal Entity Organization and Opportunities for Dispute Resolution Through Litigation - Sufiarina, Sufiarina; Alias, Nizamuddin; Sopyan, Yayan; Enijaya, Enijaya (Jurnal Hukum dan Peradilan, 2024)
Article 28 of the Indonesian Constitution is formulated to guarantee the freedom of associations and assembly, including the formation of community organizations (ormas). Ormas holding legal entity status are accommodated under associations, while non-legal entity ormas can still register but do not have the same status. The distinction between ormas and associations lies in their legal recognition. Associations possess legal entity status, while ormas are considered non-legal entities. According to Article 20 of Law No. 17 of 2013, ormas have the right to cooperate with other entities to develop and sustain their organizations. However, such cooperation may give rise to conflict, which cannot always be avoided. This raises important questions, such as "Do ormas administrators possess full authority to undertake all legal actions?" and "What avenues are available for ormas to resolve disputes through litigation?" To address these questions, doctrinal research is conducted using both legislative and conceptual methods. The results shows that the authority of ormas administrators is strictly limited by legal provisions. Since ormas lacksÂ  the legal standing required of legal entity, theyÂ  are are unable to resolve conflicts through litigation. In light of such challenges, it is recommended that ormas registration system include a comprehensive list of members authorized to act on behalf of the organizations in civil actions with third parties. This measure would enable ormas to explore non-litigation channels for resolving civil disputes, offering a practical alternative to formal court proceedings.